Literasi Informasi tentang Kemasan Produk Obat Bebas - Cahaya Purnama Dini; Puji Lestari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
This study aims to determine the motive of the public to read or understand the information contained on the drug packaging OTC, identify the ability of people to understand information on the the drug packaging OTC and the utilization of existing information. This is a qualitative research. Researchers collected data in the Kepuharjo village, Cangkringan, Sleman, Yogyakarta. The result shows that the main reason of people reading the instructions on the drug packaging OTC is to be safe after consuming drugs. However, other clue, such as drug side effects is less noticed. Because of consuming drugs is always safe, it makes people repeat in consuming drugs considered suitable for her. People do this in accordance with rules of consuming drugs because they expect to get speedy recovery. The other reason is to make as information or knowledge when they will consume drugs.